THE ACADEMIC STAFF'S PERCEPTIONS TOWARDS ONLINE EDUCATION DURING THE COVID-19 PANDEMIC - Réka KUTASI (National Centre for Policy and Evaluation in Education, 2023)
The outbreak of the COVID-19 pandemic has prompted the closure of educational institutions worldwide. As a result, most educational institutions shifted to online learning platforms to keep up with instructional activities. This study aims to determine how teachers perceive the online teaching and learning context at the George Emil Palade University of Medicine, Pharmacy, Science, and Technology of Târgu Mureş (UMPhST), Romania. An online questionnaire was created in Google Forms and sent to the academic staff at the university to evaluate the efficacy, drawbacks, and benefits of online education. A total of 139 faculty members from different departments completed the questionnaire thoroughly. According to the findings, more than half of those questioned agreed that online teaching is essential during pandemic times, but it is not a long-term solution. The difficulty of engaging students in practical activities, the lack of feedback, and the difficulty in fulfilling online assignments are just some of the challenges that were brought about. Furthermore, the survey identifies the traits of online courses the respondents preferred and additional challenges they encountered throughout this demanding time.